PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU SMKN 1 WOHA KABUPATEN BIMA - lestari, Indah; yusuf, Muhammad; Mardian, Irma (Publika Citra Media, 2025)
This study aims to determine the Effect of Compensation and Work Environment on Job Satisfaction of Teachers at SMKN 1 Wohal, Bima Regency. The approach used in the study is an associative approach. The population in the study amounted to 92 people with a sample of 38 ASN people. Data collection techniques used were observation, questionnaires, and literature studies. Data analysis techniques used were multiple linear regression analysis, correlation coefficient, determination coefficient, T test, and F test processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results of the study showed that Compensation and Work Environment simultaneously had a significant effect on Job Satisfaction of Teachers at SMKN 1 Woha, Bima Regency.